A phase 4 randomized active-controlled clinical study to compare the efficacy and safety of sustained-release pregabalin with immediate-release pregabalin in type 2 diabetic patients with peripheral neuropathic pain - Joung, Kyong Hye; Kim, Tae Nyun; Ku, Eu Jeong; Lee, Seong Su; Yoo, Won Sang; Park, Kang Seo; Kwon, Su Kyoung; Ku, Bon Jeong (Journal of diabetes and its complications, 2024)
The objective of this study was to demonstrate that sustained-release (SR) pregabalin is non-inferior to immediate-release (IR) pregabalin in attenuating diabetic peripheral neuropathic (DPN) pain along with patient satisfaction and compliance. This was an 8-week, randomized, active-controlled, open-label, phase 4 study. Eligible subjects who had been on IR pregabalin for 4 weeks were randomized to 1:1 ratio to either continue with twice-daily IR pregabalin (75 mg), or to switch to once-daily SR pregabalin (150 mg). Primary efficacy endpoint was the change in visual analogue scale (VAS) scores after 8 weeks of treatment compared to baseline in both SR and IR pregabalin groups. Among 130 randomized subjects, 125 patients were included in full analysis set. For the change in VAS pain score, the least squares (LS) mean were −17.95 (SR pregabalin) and −18.74 (IR pregabalin) and the LS mean difference between both groups was 0.79, with the upper limit of the 95 % confidence interval [−5.99, 7.58] below the pre-specified non-inferiority margin of 9.2 mm. This study demonstrates that the new once-daily SR pregabalin formulation is not different to the twice-daily IR pregabalin in alleviating DPN pain, indicating its potential as a promising treatment for DPN pain with a comparable safety profile. ClinicalTrials.gov, NCT05624853. •Efficacy, safety and patient satisfaction of sustained-release (SR) pregabalin.•SR pregabalin is non-inferior to immediate-release (IR) pregabalin in attenuating diabetic peripheral neuropathy pain.•Comparing efficacy and safety profiles between SR and IR pregabalin formulations.•Gastroretentive drug delivery system effect on diabetic peripheral neuropathy pain.